Strain localization and dynamic recrystallization in polycrystalline metals: Thermodynamic theory and simulation framework. (August 2019) - Lieou, Charles K.C.; Mourad, Hashem M.; Bronkhorst, Curt A.
Abstract: We describe a theoretical and computational framework for adiabatic shear banding (ASB) and dynamic recrystallization (DRX) in polycrystalline materials. The Langer-Bouchbinder-Lookman (LBL) thermodynamic theory of polycrystalline plasticity, which we recently reformulated to describe DRX via the inclusion of the grain boundary density or the grain size as an internal state variable, provides a convenient and self-consistent way to represent the viscoplastic and thermal behavior of the material, with minimal ad-hoc assumptions regarding the initiation of yielding or onset of shear banding. We implement the LBL-DRX theory in conjunction with a finite-element computational framework. Favorable comparison to experimental measurements on a top-hat AISI 316L stainless steel sample compressed with a split-Hopkinson pressure bar suggests the accuracy and usefulness of the LBL-DRX framework, and demonstrates the crucial role of DRX in strain localization. Highlights: We develop a model for dynamic recrystallization and adiabatic shear banding using principles of nonequilibrium statistical thermodynamics. Dynamic recrystallization is shown to be a process that minimizes the free energy of the deforming material, in accordance with the second law of thermodynamics. We perform finite-element simulations for a compressed hat-shaped stainless steel sample. The computed stress-strain response shows good agreement with the experiment, and demonstrates the essential role of dynamic recrystallization in shear localization and material softening.